ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DITINJAU DARI SELF EFFICACY SISWA - Adni, Dinda Nurul; Nurfauziah, Puji; Rohaeti, Euis Eti (IKIP Siliwangi, 2018)
The purpose of this study is to analyze and describe the ability of mathematical connections in terms of self efficacy in Triangle and Segiempat material which is guided by the mathematical connection and self efficacy indicators. This research method is descriptive research by using qualitative approach. This research was conducted in SMP Negeri in Kabupaten Bandung. The subject of this research is the students of class VIII consisting of 20 students. The instrument used in this research is a matter of mathematical connection test, non test in the form of Self efficacy questionnaire, and interview. Based on the conclusions from the results of research and discussion in general can be concluded that the ability of mathematical connections in terms of self efficacy of junior high school students is the difference in the ability of mathematical connections at each level of student self efficacy. The ability of mathematical connections in review of the student's self efficacy indicator that is not met is to apply mathematics in other fields or in everyday life, to understand the equivalent representation of a mathematical concept or procedure, to seek the relationship of various representations of concepts, processes, or mathematical procedures, procedures with other procedures in the equivalent representation. Then for the Student Self Efficacy, in completing each statement given the average student replied that students are afraid of being wrong to work on the problem, and students feel unsure that the student can do the questions given